ANALYSIS NON-PERFORMING CREDIT OF RETURN ON ASSETS AT PT. BANK SULSELBAR PERIOD 2016-2022 - Nurul Islamiyah; Nurman; Burhanuddin; Anwar Ramli; Muh. Ichwan Musa (Journal Management & Economics Review (JUMPER), 2023)
The purpose of this study was to determine the effect of non-performing loans on profitability, where profitability is the main measure of the overall success of a company. The risk of non-performing loans can cause income or profits to decrease, causing economic growth to slow down. Therefore, it is very important to know the impact of non-performing loans on return on assets. This research is a type of quantitative research. data collection techniques used to collect data on financial reports for 84 months. This research belongs to comparative causal, which measures the strength of the relationship between two or more variables to show the direction of the relationship between the independent variable and the dependent variable. Data analysis in this study uses the ROA and NPL formulas. From the results of research and discussion Return on Assets (ROA) is one of the profitability ratios that can take into account the Bank's management ability to earn overall profits. From the results of the t test research shows that NPL affects return on assets. This can be proven by the results of the t test variable NPL (X) on ROA (Y) showing a significance level of 0.475 < 0.05, it can be concluded that the NPL variable has no significant negative effect on ROA.